The Effect of Adding Different Concentration of Vitamin E to Frying Oil on the Peroxide Value (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this research is to reduce the number of peroxide in two frying oil samples (Aldura and altusan)by using one of the natural antioxidants which is vitamin E. one of the chemical specifications that assess theoil is the peroxide number, which is the amount of free radicals formed in the oil and the number of peroxidesincreases during exposure to heat, moisture, oxygen, bad storage conditions, light or other conditions. Theseperoxides have a harmful effect on the consumer health (initiation cancer). The vitamin E had a clear impacton the peroxide value, as when conducting the experiment and using oil to fry potato slices, the number ofperoxide was high before adding vitamin E which score (Peroxide number is 5.6 for 15 minutes, 9.8 for30 minutes, and 11.6 for 45 minutes). After using vitamin E in amount of 10 microgram per 100 ml of oil,the effect was clear of vitamin E on the number of peroxide as it decreased significantly. Which scored (5for 15 minutes, 8.1 for 30 minutes, 8.9 for 45 minutes). When vitamin E added by 20 microgram the resultwas (4.8 for 15 minutes, 5.5 for 30 minutes, 6.5 for 45 minutes). 50 microgram per 100 oil shown to haveno significant effect on the peroxide value. it was found that the best concentration is 20 microgram for asample of 100 ml of oil.